An English Language and Methodology Course for Training Content Area Teachers - Sabogal Patiño, Francisco Javier (Universidad Pedagógica y Tecnológica de Colombia, 2023)
This research was conducted with ten elementary school content teachers from a private educational institution in the department of Quindío in order to determine the influence of a language and methodology course on the development of teachers' professionalism and English language proficiency. To determine the impact of the course, qualitative research was carried out in which six three-hour workshops were applied and three different perspectives were gathered after each session in the form of questionnaires, a teacher's journal, and a peer observer format. According to the results, the implementation of the CBI in the course was successful because it had an impact on teachers’ perceptions, content teachers’ language proficiency and their professional development; the majority of teachers demonstrated an improvement in their English language skills.